Effects of a short-term differently dosed aerobic exercise on maximum aerobic capacity in breast cancer survivors: A pilot study - Brdareski Zorica; Đurović Aleksandar; Šušnjar Snežana; Životić-Vanović Mirjana; Ristić Anđelka; Konstantinović Ljubica; Vučković-Dekić Ljiljana; Tankosić Mirjana (Vojnosanitetski Pregled)
Background/Aim. Regular physical activity and exercise improves quality of life and possibly reduces risk of disease relapse and prolongs survival in breast cancer survivors. The aim of this study was to evaluate the impact of a 3-week moderate intensity aerobic training, on aerobic capacity (VO2max) in breast cancer survivors. Methods. A prospective, randomized clinical study included 18 female breast cancer survivors in stage I-IIIA, in which the primary treatment was accomplished at least 3 months before the study inclusion. In all the patients VO2max was estimated using the Astrand’s protocol on a bicycle-ergometer (before and after 3 weeks of training), while subjective assessment of exertion during training were estimated by the Category-Ratio RPE Scale. Each workout lasted 21 minutes: 3 minutes for warmup and cool-down each and 15 min of full training, 2 times a week. The workload in the group E1 was predefined at the level of 45% to 65% of individual VO2max, and in the group E2 it was based on subjective evaluation of exertion, at the level marked 4-6. Data on the subjective feeling of exertion were collected after each training course in both groups. Results. We recorded a statistically significant improvement in VO2max in both groups (E1 - 11.86%; E2 - 17.72%), with no significant differences between the groups. The workload level, determined by the percent of VO2max, was different between the groups E1 and E2 (50.47 ± 7.02% vs 55.58 ± 9.58%), as well as subjective perception of exertion (in the groups E1 and E2, 11.6% and 41.6% of training, respectively, was graded in the mark 6). Conclusion. In our group of breast cancer survivors, a 3-week moderate intensity aerobic training significantly improved the level of VO2max.